Community-based early learning in Solomon Islands: cultural and contextual dilemmas influencing program sustainability - Burton, L (2011)
The Solomon Islands (SI), a small developing nation in the South Pacific, demonstrates an emergent community-based kindergarten model with the potential to promote context and culture relevant early learning and development. SI early childhood education (ECE) particularly rose in prominence with a 2008 national policy enactment requiring all children to attend three years of kindergarten as prerequisite for primary school entry. However, these ECE programs remain severely challenged by faltering community support. Internationally, many ECE programs dramatically resemble a universalized Western-based model, with a decidedly specific discourse for “high quality” programs and practices for children ages 0-8. Often these uncritical international transfers of Euro-American ideologies promote restricted policies and practices. This has resulted in a self-perpetuating set of practices and values, which arguably prevent recognition of, and efforts to reinvent, more culturally-relevant, sustainable programs for the Majority World. Based on the Kahua region (est. pop. 4,500) of Makira-Ulawa Province, this collaborative, ethnographically-inspired, case study explores how community characteristics have affected the cultural and contextual sustainability of community-based ECE in remote villages. The study traces historical and cultural influences to present-day SI ECE. Subsequently, it explores the re-imagined SI approach to formal ECE program design, remaining challenges preventing these programs from being sustained by communities, and potential community-wide transformations arising from these initiatives. To achieve this, the study collaborated with stakeholders from all levels of SI society through extensive participant-observations, interviews, and participatory focus groups. Findings aspire to enlighten regional sustainable developments and resilient behaviors relating to ECE. Key research findings suggest five overarching principles influencing kindergarten sustainability: presence of “champion” for the ECE vision; community ownership-taking, awareness-building, and cooperation-maintenance; and program cultural/contextual sensitivity and relevance. These elements were found to be strongly linked with an intergenerational cultural decay in the Kahua region, as conceptualized through a model of Cyclically-Sustained Kindergarten Mediocrity.